Base‐Biased Evolution of Disease‐Associated Mutations in the Human Genome. Issue 11 (31st August 2016) - Xue, Cheng; Chen, Hua; Yu, Fuli
Abstract : Via analyzing several large‐scale human datasets, we found that mutation rate per base varies in a wide range (∼8X‐10X), which is the cause of base‐biased evolution. In this study we have showed how mutation, recombination and selection are working together in shaping the base‐biased evolution of mutations. As a special subset, disease‐associated mutations follow this evolutionary rule. Therefore our study is helpful in explaining the distribution pattern of disease‐associated mutations. ABSTRACT: Understanding the evolution of disease‐associated mutations is fundamental to analyze pathogenetics of diseases. Mutation, recombination (by GC‐biased gene conversion, gBGC), and selection have been known to shape the evolution of disease‐associated mutations, but how these evolutionary forces work together is still an open question. In this study, we analyzed several human large‐scale datasets (1000 Genomes, ESP6500, ExAC and ClinVar), and found that base‐biased mutagenesis generates more GC→AT than AT→GC mutations, while gBGC promotes the fixation of AT→GC mutations to balance the impact of base‐biased mutation on genome. Due to this effect of gBGC, purifying selection removes more deleterious AT→GC mutations than GC→AT from population, but many high‐frequency (fixed and nearly fixed) deleterious AT→GC mutations are remained possibly due to high genetic load. As a special subset, disease‐associated mutations follow this evolutionary rule, in which disease‐associated GC→AT mutations are more enriched in rare mutations compared with AT→GC, while disease‐associated AT→GC are more enriched in mutations with high frequency. Thus, we presented a base‐biased evolutionary framework that explains the base‐biased generation and accumulation of disease‐associated mutations in human populations.